Inhibited fatty acid β-oxidation impairs stress resistance ability in Nile tilapia (Oreochromis niloticus). Issue 68 (September 2017) - Pan, Han; Li, Ling-Yu; Li, Jia-Min; Wang, Wei-Li; Limbu, Samwel Mchele; Degrace, Pascal; Li, Dong-Liang; Du, Zhen-Yu
Abstract: Energy metabolism plays important roles in stress resistance and immunity in mammals, however, such functions have not been established in fish. In the present study, Nile tilapia ( Oreochromis niloticus ) was fed with mildronate, an inhibitor of mitochondrial fatty acid (FA) β-oxidation, for six weeks subsequently challenged with Aeromonas hydrophila and ammonia nitrogen exposure. Mildronate treatment reduced significantly l -carnitine concentration and mitochondrial FA β-oxidation efficiency, while it increased lipid accumulation in liver. The fish with inhibited hepatic FA catabolism had lower survival rate when exposed to Aeromonas hydrophila and ammonia nitrogen. Moreover, fish fed mildronate supplemented diet had lower immune enzymes activities and anti-inflammatory cytokine genes expressions, but had higher pro-inflammatory cytokine genes expressions. However, the oxidative stress-related biochemical indexes were not significantly affected by mildronate treatment. Taken together, inhibited mitochondrial FA β-oxidation impaired stress resistance ability in Nile tilapia mainly through inhibiting immune functions and triggering inflammation. This is the first study showing the regulatory effects of lipid catabolism on stress resistance and immune functions in fish. Highlights: Limited carnitine synthesis inhibited mitochondrial FA β-oxidation and impaired stress resistance ability in Nile tilapia. Inhibited mitochondrial FA β-oxidation impaired immune functions and triggered inflammation. Lipid catabolism had regulatory effects on stress resistance and immune functions in fish.